An evaluation of environmental, intrinsic and pre- and post-slaughter risk factors associated to dark-cutting beef in a Federal Inspected Type slaughter plant. (April 2019) - Loredo-Osti, Jorge; Sánchez-López, Eduardo; Barreras-Serrano, Alberto; Figueroa-Saavedra, Fernando; Pérez-Linares, Cristina; Ruiz-Albarrán, Miguel; Domínguez-Muñoz, Miguel Ángel
Abstract: The objective was to determine the risk factors associated to dark-cutting in bovine carcasses. The study was conducted at a Federal Inspection abattoir located in northeastern Mexico. A random sample of 394 animals at slaughter was used. A total of 26 explanatory variables were evaluated; the analysis included environmental, animal-specific, and management factors both at pre- and post- slaughter periods. Only four variables were statistically significant within the final logistic regression model ( P < .001). The frequency of dark-cutting carcasses was 13.45%. Lairage time was directly proportional to the percentage of risk for dark-cutting beef. Improper desensitization also increased the frequency of carcasses with this anomaly. Backfat thickness and the 24-h pH differential of the carcasses were inversely proportional to the risk for dark-cutting beef. An interesting finding was that risk factors for DFD meat are present in all stages of the slaughter process and thus to effectively address this problem an integral evaluation is needed throughout the slaughter process.